Is there a role for an orthogeriatric model of care for the management of vertebral fragility fractures in hospital? - Ong, Terence (2019)
Introduction: Orthogeriatric care has led to improved outcomes in the management of patients admitted to hospital with hip fractures. Such an interprofessional multidisciplinary collaboration ensured that the complex needs of older people with hip fractures are met. This thesis considered the role of an orthogeriatric model of care for patients in hospital with vertebral fragility fractures. To support such a care model, certain conditions had to be met. The number of patients admitted to hospital warrant such a service, these patients have complex care needs, their outcomes poor and that hospital care had to be delivered by healthcare professionals with specific knowledge and skills.